The Influence of Training, Discipline, Intrinsic Motivation and Competence on Employee Performance with Employee Behavior as a Mediating Variable - Febrian, Wenny Desty; Nuraeni, Nuraeni; Faisal, Ahmad; Gani, Intan Maesti (International Journal of Advanced Multidisciplinary, 2024)
The article on the influence of training, discipline, intrinsic motivation and competence on employee performance with consumer behavior as a mediating variable is a scientific literature article in the scope of human resource management science. The purpose of this study is to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of marketing management. The research method used is descriptive qualitative. The data collection technique uses literature studies. Data were obtained from previous studies that are relevant to this study and sourced from academic online media such as Publish or Perish, Google Scholar, digital reference books and Sinta journals. The results of this article are: 1) Training influences Employee Behavior; 2) Discipline influences Employee Behavior; 3) Intrinsic Motivation influences Employee Behavior; 4) Competence influences Employee Behavior; 5) Training influences Employee Performance; 6) Discipline influences Employee Performance; 7) Intrinsic Motivation influences Employee Performance; 8) Competence influences Employee Performance; and 9) Employee Behavior influences Employee Performance.